Reproductive performance of small ruminants in an outreach pilot project in West Java - Setiadi, B.; ., Subandriyo; Iniguez, L. C. (Indonesian Journal of Animal and Veterinary Sciences, 1995)
Reproductive performance of small ruminants was evaluated in an on-farm multidisciplinary research project, known as the outreach pilot project (OPP), involving village farms in West Java, Indonesia . Strategies to increase production of small ruminants were implemented in this project . Data from three consecutive years (1986-87, 1987-1988 and 1988-1989) showed no significant increase in flock size . Average number of ewes per farm per month (EA) was 4 .1 . Although on average, larger farms had lower flock performance, a few individual farms with large flocks performed outstandingly in both reproduction and production . Twenty-eight percent of the farms had averaged 10 month lambing intervals (LI) with a potential of 3 lambings every 2 years (8 months interval) . Most of the differences between years were mainly due to changes in farm average litter size (FLS) (P<0.05) and changes in lamb mortality (%M) (P>0.05) : from 1 .33 and 20.5% to 1 .57 and 10 .4% ; for averages of FLS and %M between years 1986-87 and 1987-89, respectively. These changes were reflected in an increase in the number of lambs weaned per year per ewe available (LWEA) from 1 .19 in year 1 to 1 .60 in years 2 and 3, and were assumed to be promoted by the on-farm research program . Farms with large FLS in spite of higher %M, contributed a net improvement in LWEA and kilograms of lambs weaned. A different range of 3 .9-4 .5 kg of lambs weaned was found between the top 4 and the bottom 6 farms for FLS (averaging 2 .09 and 1 .19, respectively, for FLS) . Litter sizes 2 and 3 contributed substantial improvement in ewe productivity, weaning 18 and 23 kg of lambs, respectively . Key words : Small ruminants, reproductive performance, village farms, West Java